Chronic Treatment with Anti-bipolar Drugs Down-Regulates Gene Expression of TRPC1 in Neurones - Du, Ting; Rong, Yan; Feng, Rui; Verkhratsky, Alexei; Peng, Liang (Frontiers in Cellular Neuroscience, 2017)
In the brain, TRPC1 channels are abundantly expressed in neurones virtually in all regions; these proteins function as receptor-activated ion channels and are implicated in numerous processes, being specifically important for neurogenesis. Primary cultures of mouse cerebellar granule cell, cerebral cortical neurones and freshly isolated neurones from in vivo brains were used to study effects of chronic treatment with anti-bipolar drugs (carbamazepine (CBZ), lithium salts and valproic acid) on gene expression of TRPC1. Expression of TRPC1 mRNA was identified with reverse transcription-polymerase chain reaction (RT-PCR), whereas protein content was determined by Western blotting. Store-operated plasmalemmal Ca2+ entry (SOCE) was measured with fura-2 based microfluorimetry. Chronic treatment with each of the three drugs down-regulated mRNA and protein expression in cultured cerebellar granule cells in a time- and concentration-dependent manner. Similar effect was also observed in cultured cerebral cortical neurones treated with CBZ and in freshly isolated neurones from the brains of CBZ-treated animals. The amplitude of SOCE was substantially decreased in cerebellar granule cells chronically treated with each of the three drugs. Our findings indicate that down-regulation of TRPC1 gene expression and function in neurones may be one of the mechanisms of anti-bipolar drugs action.